Diagnostic Potential of Imaging Flow Cytometry. Issue 7 (July 2018) - Doan, Minh; Vorobjev, Ivan; Rees, Paul; Filby, Andrew; Wolkenhauer, Olaf; Goldfeld, Anne E.; Lieberman, Judy; Barteneva, Natasha; Carpenter, Anne E.; Hennig, Holger
Abstract : Imaging flow cytometry (IFC) captures multichannel images of hundreds of thousands of single cells within minutes. IFC is seeing a paradigm shift from low- to high-information-content analysis, driven partly by deep learning algorithms. We predict a wealth of applications with potential translation into clinical practice.